Application of rivaroxaban in patients with non-valvular atrial fibrillation and end-stage kidney disease: A systematic review and meta-analysis - Yang, Zhenzhen; Wang, Jieya; Yuan, Ye; Cheng, Tian; Ren, Feifei; Wang, Songsong; Zhang, Zhiqing (Frontiers in Cardiovascular Medicine, 2023)
Background Nowadays, the number of patients with non-valvular atrial fibrillation (NVAF) complicated by end-stage renal disease (ESKD) is increasing. There are significant challenges in anticoagulation with prescription drugs because of the high risk of bleeding and embolism among these patients. However, no randomized controlled trials (RCTs) of warfarin in combination with any non-vitamin K oral anticoagulant (NOACs) have been performed in patients with baseline creatinine clearance (CrCl) <25 ml/min, which makes it difficult to justify the use of anticoagulants in such patients. Then, we aimed to collect and summarize all evidence to enable the anticoagulation of rivaroxaban, which is less cleared by the kidneys, in patients with severe renal insufficiency and to complement and improve the evidence on the use of rivaroxaban for anticoagulation. Methods The present systematic review and meta-analysis searched the databases of PubMed, Embase, the Cochrane Library, CNKI, CBM, and Google Scholar for relevant studies from inception to 1 June 2022, with the restriction of English and Chinese. Eligible cohort studies and RCTs that reported efficacy outcomes [composite of stroke and systemic embolism (SSE), ischemic stroke (ICS), and systemic embolization] or safety outcomes [major bleeding, intracranial hemorrhage (ICH), and gastrointestinal bleeding (GIB)] of rivaroxaban in NVAF patients with ESKD were enrolled. Two authors completed the data extraction and quality assessment work, respectively. The Cochrane Collaboration tool for assessing the risk of bias was used for RCTs, and the NEW-Castle Ottawa scale was used for study quality assessment for cohort studies. Dichotomous variables were calculated as risk factors with 95% confidence intervals (CIs), and meta-analysis was performed to probe the effect of research design, rivaroxaban dose, and controlled drug factors on outcomes. Results In total, three studies were included for meta-analysis, involving 6,071 NVAF patients with ESKD, and two studies were included for qualitative analysis. All included studies were at low risk of bias. A meta-analysis demonstrated that mix-dose rivaroxaban caused no statistical discrepancy in the occurrence of thrombotic and bleeding events when compared to the control group (embolism, LogOR: −0.64, 95% CI: −1.05 to −0.23, P:0.25; bleeding, LogOR: −0.33, 95% CI: −0.63 to −0.03, P:0.15), and low-dose rivaroxaban produced similar results (embolism, LogOR: −1.04, 95% CI: −2.15 to 0.07, P:0.61; bleeding, LogOR: −0.81, 95% CI: −1.19 to −0.44, P:0.93). Conclusion In this study, low-dose rivaroxaban (10 mg, once a day) may benefit more than warfarin in patients with NVAF and ESKD. Systematic review registration https://www.crd.york.ac.uk/prospero/#recordDetails, identifier CRD42022330973.